Manipulating Individual State During Migration: Carry‐Over Effects of Cumulative Stress on Survival - Ilona P. Grentzmann; Gilles Gauthier; Frédéric Angelier; Joël Bêty; Frédéric LeTourneux; Pierre Legagneux (Ecology and Evolution)
ABSTRACT The stress response is a mechanism to cope with unpredictable events and minimize immediate threats to survival. However, cumulated stress due to multiple stressors can have long‐term deleterious effects on fitness by impairing reproduction and survival. This aspect of stress physiology and its consequences on demographic traits have received little attention in wild populations, and such studies are mostly observational. Here, we investigate the demographic consequences of multiple stressors (fasting and prolonged captivity) experimentally imposed during spring migration on greater snow geese (Anser caerulescens atlantica). In 2009, female snow geese were captured at a spring staging site and kept in captivity for up to 4 days with or without access to food. Blood samples were taken at capture, banding, and release to measure corticosterone (CORT) levels, a stress‐response hormone, during the experiment. CORT response peaked within the first hours after capture and decreased during the following days in captivity. We observed that stress‐induced CORT levels of captive individuals at release depended on their pre‐experiment body condition, but not the stress‐induced peak CORT response. We showed no link with subsequent reproductive success, but we detected a negative carry‐over effects of food deprivation on survival in the following year. Pre‐treatment spring body condition and stress‐induced CORT levels had marginal effects on survival. We showed that cumulated stressors could have carry‐over effects on survival and that the intensity of the hormonal response can ultimately affect survival.